A relation between embedding degrees and class numbers of binary quadratic forms - Ling, San (2015)
In this paper, we describe a relation between the em-bedding degree of an elliptic curve over a prime eld Fp and the inertial degree of the primes above p in a certain ring class eld. From this relation, we conclude that the embedding degree divides the class number of a group of binary quadratic forms of a xed discriminant.